Analisis Peningkatan Pengetahuan dan Keterampilan Kader Setelah Pelatihan Deteksi Dini Stunting di Kecamatan Tayan Hilir Kabupaten Sanggau - Nur Aini; Marlenywati Marlenywati; Indah Budiastutik; Elly Trisnawati; Widya Fermata; Eka Puspita Sari (Ghidza: Jurnal Gizi dan Kesehatan, 2025)
Stunting remains a child health problem because it affects physical growth and cognitive development. Posyandu cadres have a strategic role in early detection of stunting, but their knowledge and skills need to be improved. This study aims to evaluate changes in cadres' knowledge and skills after early detection training on stunting.  A quantitative, quasi-experimental study (one group pre-test and post-test design) was conducted on 40 posyandu cadres using a purposeful sampling technique. The instrument consisted of 20 questions (scored 0–20) assessing the cadres' knowledge and skills. Improvement in training outcomes was measured through pre-test and post-test analyzed using paired t-test. The average score increased from 11.60 ± 5.295 to 15.18 ± 5.028. The average difference in increase was 3.58. A P-Value of 0.000 was found in the results of the paired t-test, confirming that the training intervention had a very significant effect on improving cadre knowledge. Early detection training on stunting significantly improved the knowledge and skills of integrated health post (Posyandu) cadres, strengthening stunting prevention efforts in the community.